Integrative Analysis of MUC4 to Prognosis and Immune Infiltration in Pan-Cancer: Friend or Foe? - Gao, Xiao-Peng; Dong, Jie-Jie; Xie, Tian; Guan, Xiaoqing (Frontiers in Cell and Developmental Biology, 2021)
MUC4, a transmembrane mucin, plays important roles in epithelial renewal and differentiation. Recent studies suggest that MUC4 has been implicated in the pancreatic cancer pathogenesis and is expressed in various normal and cancer tissues. Underlying the features of MUC4 across various cancer types may allow us to ensure appropriate treatment and patient monitoring. However, the contributions of MUC4 to pan-cancer have not been well characterized. In this study, we investigated the expression pattern and prognostic value of MUC4 across multiple databases. We further explored genomic and epigenetic alteration of MUC4, its association with proliferation and metastasis, and correlation with immune infiltration in different cancers. Our results characterized the distinct expression profile and prognostic values of MUC4 in pan-cancer. Through examining its association with genomic alteration, tumor proliferation and metastasis, as well as tumor infiltrating, we revealed multiple function effects of MUC4. MUC4 may influence prognosis, proliferation, metastasis, and immune response in opposite directions. In conclusion, our findings suggested the necessity to more carefully evaluate MUC4 as biomarker and therapeutic target, and develop the new antibodies for cancer detection and intervention.